Weibull distribution analysis of wind energy prospect for Umudike, Nigeria for power generation. (February 2019) - Aririguzo, Julian C.; Ekwe, Ekwe B.
Highlights: Strategic application of Weibull distribution two-parameter model. High potential for application of Wind Energy Conversion Systems (WECS). Wind speeds expected at 30 m altitude corresponds to peak values for optimal wind turbine operation. Abstract: This paper is the first and preliminary part of a broader project in the Niger Delta to tap into a vast sustainable source of energy to generate electricity from wind energy in three cities in Eastern Nigeria namely Warri, Umuahia and Owerri. An important and integral part of the project is assessment or investigation of viability of available wind in these locations to facilitate localized wind blade modeling, design and manufacturing, for potential power generation. This research presents a detailed analysis of wind profile and wind prospect in one of the three cities – Umudike (Umuahia), using Weibull distribution two-parameter model. The overall result shows enormous potentials for application of wind energy conversion systems (WECS), and hence it can be safely concluded that the available wind energy in Umudike (Umuahia), Nigeria is feasible for the proposed scheme.